Pengetahuan Orang Tua dengan Anak Tuberkulosis di RSUD dr. Soeselo Tegal: Knowladge Among Parents about Pediatric Tuberculosis in RSUD dr. Soeselo Tegal - Farah Nibras Almira; Windy Rakhmawati; Sri Hendrawati; Nenden Nur Asriyani Maryam (Jurnal Surya Medika (JSM), 2023)
Parents' knowledge about pediatric tuberculosis which still has high insidence is needed because it will affect the attitudes and health-seeking behavior of parents. If parents’ knowledge is poor, it can inhibit pediatric tuberculosis control program. This study aimed to describe the parents’ knowledge about pediatric tuberculosis in dr. Soeselo Tegal. Research design, namely descriptive quantitative with cross-sectional approach through total sampling with a sample of 35 people. The instrument used to collect data was the result of developing instrument points in the KAP (Knowledge, Attitude, and Practice Survey) issued by WHO in 2008. The results of this study obtained that 22 respondents (62.9%) had good knowledge and 13 respondents (37, 1%) with poor knowledge. Parents' knowledge is not good regarding TB signs and symptoms in children has the highest frequency because it is often difficult to distinguish between TB sign and symptoms in children and other diseases, so many parents are late to bring their children to the hospital for examination and treatment. Therefore, nurses are suggested to educate parents regarding tuberculosis in children.